2022
DOI: 10.1149/1945-7111/ac9f71
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Testing of Commercial Rechargeable Lithium Polymer Batteries for Small Satellite Applications

Abstract: Commercial-off-the-shelf (COTS) electrical components are becoming of interest for small satellite applications due to their accessibility, good performance, and low cost. We quantify the performance of Lithium Polymer (LiPo) COTS batteries under irradiation to assess their reliability. LiPo battery cells with LiCoO2 cathodes, nominal voltages of 3.7 V, and rated capacities of 6000 mAh are irradiated with a 30 MeV proton beam from the Middle East Technical University Defocusing Beamline, which delivers a maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…There are also demands for batteries to be used in mobile equipment for surveying, sampling, or rescue efforts under radiation environments, such as in the scenario of the 2011 Fukushima nuclear accident. [33,34] However, conventional LIBs cannot run for long enough under the radiation environment because of the electrode and electrolyte failures. Cao et al found that the grain size of LiFePO 4 increased after neutron and gammaray irradiation, and as a result, irradiated cells showed increased resistance by threefold.…”
Section: Other Extreme Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also demands for batteries to be used in mobile equipment for surveying, sampling, or rescue efforts under radiation environments, such as in the scenario of the 2011 Fukushima nuclear accident. [33,34] However, conventional LIBs cannot run for long enough under the radiation environment because of the electrode and electrolyte failures. Cao et al found that the grain size of LiFePO 4 increased after neutron and gammaray irradiation, and as a result, irradiated cells showed increased resistance by threefold.…”
Section: Other Extreme Conditionsmentioning
confidence: 99%
“…[30][31][32] Moreover, radiation conditions often have to be considered for battery applications in satellites and spaceships. [33,34] These extreme conditions pose significant challenges to currently developed batteries because of the limitations on battery electrode materials, electrolytes, and packaging materials (Figure 1).…”
Section: Introductionmentioning
confidence: 99%